2022
DOI: 10.1039/d1nj05858d
|View full text |Cite
|
Sign up to set email alerts
|

The Pt/g-C3N4-CNS catalyst via in situ synthesis process with excellent performance for methanol electrocatalytic oxidation reaction

Abstract: This paper prepared graphite carbon nitride (C3N4) and carbon nanosheet (CNS) composite supporter (g-C3N4-CNS) by in situ synthesis (IS), and the effect of Pt-based catalyst on methanol electrocatalytic oxidation (MOR)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…[ 378 ] However, the Pt/g‐C 3 N 4 catalyst has a stronger ability to reduce CO 2 to CH 4 , which is the main product of this reaction. [ 379 ] Similarly, Su et al. [ 380 ] used DFT to investigate the mechanism of the improved catalytic activity of S‐doped g‐C 3 N 4 .…”
Section: Theoretical Studies Of G‐c3n4mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 378 ] However, the Pt/g‐C 3 N 4 catalyst has a stronger ability to reduce CO 2 to CH 4 , which is the main product of this reaction. [ 379 ] Similarly, Su et al. [ 380 ] used DFT to investigate the mechanism of the improved catalytic activity of S‐doped g‐C 3 N 4 .…”
Section: Theoretical Studies Of G‐c3n4mentioning
confidence: 99%
“…[378] However, the Pt/g-C 3 N 4 catalyst has a stronger ability to reduce CO 2 to CH 4 , which is the main product of this reaction. [379] Similarly, Su et al [380] used DFT to investigate the mechanism of the improved catalytic activity of S-doped g-C 3 N 4 . It was found that in the case of S atom, there are three potential doping sites, named N Aro , N Cen , and N Tet , respectively, and the NTet sites are the ones connected to the three nearest heptazine rings (Figure 15a).…”
Section: Theoretical Studies Of G-c 3 Nmentioning
confidence: 99%